Efficacy and Safety of Lumen Apposing Self-Expandable Metal Stents for EUS Guided Cholecystostomy: A Meta-Analysis and Systematic Review. (12th April 2018) - Kalva, Nikhil R.; Vanar, Vishwas; Forcione, David; Bechtold, Matthew L.; Puli, Srinivas Reddy
Abstract : Background . Patients with acute cholecystitis are treated with early cholecystectomy. A subset of patients are unfit for surgery due to comorbidities and late presentation. Prompt gall bladder drainage (GBD) with percutaneous or endoscopic approach remains a viable therapeutic option for nonoperative candidates. Endoscopic ultrasound (EUS) guided transluminal gall bladder drainage (EUS-GBD) continues to evolve as an alternative approach to percutaneous drainage. With continued refinement in stent technology, lumen apposing self-expandable metal stent (LAMS) offers several advantages. We performed a pooled analysis on the efficacy and safety of EUS-GBD with LAMS in nonoperative candidates with acute cholecystitis. Methods . Extensive English language literature search was performed in Medline, Embase, Cochrane Central, and Google Scholar using keywords "endoscopic ultrasound", "stent", "gallbladder", "acute cholecystitis", and "cholecystostomy" from Jan 2000 to Dec 2016. Fixed and random effects models were used to calculate the pooled proportions. Results . Data was extracted from 13 studies that met the inclusion criteria( n = 233 ) . Pooled proportion of technical success was 93.86% (95% CI = 90.56 to 96.49) and clinical success was 92.48% (95% CI = 88.9 to 95.42). Overall complication rate was 18.31% (95% CI = 13.49 to 23.68) and stent related complication rate was 8.16% (95% CI = 4.03 to 14.96) in the pooled percentage of patients. Pooled proportion for perforation was 6.71% (95% CI 3.65 to 10.6) and recurrent cholangitis/cholecystitis was noted in 4.05% (95% CI = 1.64 to 7.48). Publication bias calculated using Harbord-Egger bias indicator gave a value of −0.61 (95%    CI = −1.39 to 0.16, p = 0.11 ). The Begg-Mazumdar indicator for bias gave Kendall's taub value of −0.42( p ≥ 0.05 ) . Conclusions . EUS-GBD with LAMS is a safe and alternative treatment modality for patients needing gallbladder drainage, with acceptable intraprocedural and postprocedural complications. However, due to the limited data and lack of direct comparison with other methods, further controlled trials are necessary to estimate the overall efficacy and safety and the role of EUS-GBD with LAMS in management of nonoperative patients with acute cholecystitis.